Diverse Intercropping Patterns Enhance the Productivity and Volatile Oil Yield of Atractylodes lancea (Thunb.) DC. - Peng, Zheng; Zhang, Yan; Yan, Binbin; Zhan, Zhilai; Chi, Xiulian; Xu, Yang; Guo, Xiuzhi; Cui, Xinping; Wang, Tielin; Wang, Sheng; Kang, Chuanzhi; Wan, Xiufu; et al. (Frontiers in Plant Science, 2021)
Commercial cultivation of the medicinal plant Atractylodes lancea is significantly restricted by low survival rates and reduced yields. Intercropping can reasonably coordinate interspecific interactions, effectively utilize environmental resources, and increase survival and yield. We conducted a field experiment from 2014 to 2016 to analyze the advantages and effects of intercropping on A. lancea survival, growth traits, individual volatile oil content, and total volatile oil content. In addition to A. lancea monoculture (AL), five intercropping combinations were planted: Zea mays L. (ZM) + A. lancea, Tagetes erecta L. (TE) + A. lancea, Calendula officinalis L. (CO) + A. lancea, Glycine max (Linn.) Merr. (GM) + A. lancea, and Polygonum hydropiper L. (PH) + A. lancea. The survival and average rhizome weight of A. lancea was higher in the ZM, CO, and TE treatments than in the monoculture treatment, and the average plant height was higher in all intercropping treatments than in the monoculture. The volatile oil content of A. lancea from the ZM and CO treatments was significantly improved relative to that of monoculture plants. The volatile oil harvest was higher in the ZM, CO, and TE treatments than in the monoculture. We conclude that intercropping is an effective way to increase the survival and yield of A. lancea. Furthermore, intercropping with ZM, CO, and TE increases the harvest of four volatile oils from A. lancea.